Online Formative Assessments in Medical Education During COVID-19 - Sharma, Sonali; Jha, Manju (Journal of Nepal Health Research Council, 2024)
Background: This study aimed to evaluate perception of medical students regarding online mode of assessments and to compare the academic outcomes of various methodologies adopted for online formative assessments. Methods: This was a descriptive cross-sectional study. This study was conducted in the department of biochemistry at the constituent medical college of Health University in India and included 150 first year medical undergraduates of either gender. The institutional ethical clearance and written informed consent was taken prior to the study from all the enrolled participants. A series of online formative assessments were designed in the form of multiple choice, short answer questions, case-based learning, and viva-voce to satisfy each learning outcome. Google platform was used for conducting online formative assessment. The participants were asked to fill questionnaire based on 5-point Likert scale to obtain information on challenges and perceptions related to OFA. Academic performance was evaluated and compared for various modes of assessments. Results: The mean age of the participants was 19.34Â±0.947 years. Most of the students were from urban areas and majority (73.33%) preferred MCQs. 60.67% respondents favored conduction of e-assessments. 80.67% of students agreed that solving clinical cases in the online assessments contributed to clinical learning. Conclusions: Formative online assessment can be used as an intervention to reshape medical education sector during times when infection controls and physical isolation measures are crucial to avoid spread of disease. Keywords: Formative assessment; medical education; online assessment.